Dynamics of soil exploration by fine roots down to a depth of 10 m throughout the entire rotation in Eucalyptus grandis plantations - Laclau, Jean-Paul; Silva, Eder A.; Rodrigues Lambais, George; Bernoux, Martial; le Maire, Guerric; Stape, José Luiz; Bouillet, Jean-Pierre; Gonçalves, José leonardo M.; Jourdan, Christophe; Nouvellon, Yann (Frontiers in Plant Science, 2013)
Although highly weathered soils cover considerable areas in tropical regions, little is known about exploration by roots in deep soil layers. Intensively managed Eucalyptus plantations are simple forest ecosystems that can provide an insight into the belowground growth strategy of fast-growing tropical trees. Fast exploration of deep soil layers by eucalypt fine roots may contribute to achieving a gross primary production (GPP) that is among the highest in the world for forests. Soil exploration by fine roots down to a depth of 10 m was studied throughout the complete cycle of Eucalyptus plantations. Intersects of fine roots, less than 1 mm in diameter, and medium-sized roots, 1-3 mm in diameter, were counted on trench walls in a chronosequence of 1-, 2-, 3.5- and 6-year-old plantations on a sandy soil, as well as in an adjacent 6-year-old stand growing in a clayey soil. Two soil profiles were studied down to a depth of 10 m in each stand (down to 6 m at ages 1 and 2 years). The root intersects were counted on 224 m2 of trench walls in 15 pits. Monitoring the soil water content showed that, after clear-cutting, almost all the available water stored down to a depth of 7 m was taken up by tree roots within 1.1 year of planting. The soil space was explored intensively by fine roots down to a depth of 3 m from 1 year after planting, with an increase in anisotropy in the upper layers throughout the stand cycle. About 60% of fine root intersects were found at a depth of more than 1 m, irrespective of stand age. The root distribution was isotropic in deep soil layers and kriged maps showed fine root clumping. The results showed that a considerable volume of soil was explored by fine roots in eucalypt plantations on deep tropical soils, which might prevent water and nutrient losses by deep drainage after canopy closure and contribute to maximizing resource uses.